Diamphotoxin : the arrow poison of the !Kung Bushmen - De la Harpe, Jonathan H (Division of Chemical Pathology, 2018)
In this thesis I describe a toxic protein, diamphotoxin, that is present in the pupae of the beetle Diamphidia nigro-ornata. This insect is used as an arrow poison by the !Kung Bushmen inhabiting the savannah of eastern Namibia and western Botswana. Preliminary investigations showed that the pupae contained a 3,7 S cationic protein which caused haemolysis and, after intramuscular injection, local paralysis followed by death. By intravenous lethality assay, one 200 mg pupa contained 20 000 mouse lethal doses. Assays for the toxin were developed based upon haemolysis in vitro and lethality in vivo. These assays were used to monitor purification of the toxin. Diamphotoxin was purified by acid extraction in 0,1M glycine-HCl pH 3,0 followed by ammonium sulphate fractionation, chromatography on hydroxyl apatite, phosphocellulose and, finally, on DEAE cellulose. A consistent increase in activity after the hydroxyl apatite chromatography pointed to the removal of an inhibitor during this step. A subsequent severe loss of activity after chromatography on phosphocellulose could neither be explained nor overcome. The phosphocellulose chromatography step yielded three peaks of toxic activity. Immunological studies revealed cross-reactivity but not identity between these three toxin species. The toxin in the first peak to elute from the phosphocellulose column was purified to electrophoretic homogeneity by chromatography on DEAE cellulose. Attempts to purify the toxin in the other two phosphocellulose peaks were not successful. The isolated molecule was confirmed to be the toxin by haemolysis in a blood-agarose underlay after SDS-gel electrophoresis. The molecular weight estimate for the toxin by SDS-gel electrophoresis was 60 700 daltons and by analytical ultracentrifugation 62 100 daltons. The molecule appeared to exist as a single polypeptide chain. The amino acid composition showed a high proportion of hydrophobic amino acids. Isoelectric focussing showed an isoelectric point of pH 9,45. Toxin mediated haemolysis was studied in detail. The haemolytic event could be broken down into two stages. In the first stage toxin bound irreversibly to the cell but, provided no divalent cations were present, no damage to the cell could be detected. The second stage required the presence of free calcium (or certain other divalent cations), with an optimum concentration at 1 mM. The interaction of calcium with the cell-bound toxin resulted in the cell membrane becoming highly permeable to Na⁺ and K⁺ ions. Experiments designed to detect phospholipase or protease activity in toxin solutions gave negative results. Erythrocytes incubated with ¹²⁵I-labelled pure toxin in calcium-free medium retained a quantity of bound toxin which could not be removed by repeated washing. Incubation of erythrocytes with calcium-free toxin resulted in depletion of the activity of the toxin solution. The kinetics of the haemolytic action of the toxin were shown to be stoichiometric rather than catalytic. It was estimated that haemolysis by the toxin required a minimum of approximately 100 molecules per cell. Studies using circular dichroism measurements and the fluorescent probe 8-anilino-1-naphthalene sulphonic acid (ANS) indicated that a conformational change occurred in the toxin upon exposure to calcium. The ANS studies indicated that upon the addition of calcium the toxin molecule became more hydrophobic. It was concluded that the toxin functions as a calcium regulated Na⁺ and K⁺ ionophore in that it binds to the cell membrane and, in the presence of calcium or certain other divalent cations, assumes a conformation which mediates the free passage of Na⁺ and K⁺ ions. The resultant disruption of normal transmembranous ionic concentration gradients leads to cell lysis by loss of osmoregulation and, in the case of excitable membranes, disruption of electrophysiological activity.